The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s12247-021-09568-z
|View full text |Cite
|
Sign up to set email alerts
|

Core-Shell Nanofibers Based on Polycaprolactone/Polyvinyl Alcohol and Polycaprolactone/Collagen for Biomedical Applications

Abstract: Coaxial electrospinning is a robust technique to prepare core-shell nanofibers for various biomedical applications such as tissue engineering. In this study, the coaxial electrospinning method was used to prepare two different core-shell nanofibers based on polycaprolactone/polyvinyl alcohol (PCL/PVA) and polycaprolactone/collagen (PCL/Col). The mechanical (e.g., shear viscosity and surface tension) and chemical properties of the nanofibers were characterized and compared. The results showed that PCL/Col nanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…If the surface tension is low, the formation of the jet begins at a lower voltage. The surface tension of polymer solution can be changed by varying solvents and by adding surfactants [26,41].…”
Section: Surface Tensionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the surface tension is low, the formation of the jet begins at a lower voltage. The surface tension of polymer solution can be changed by varying solvents and by adding surfactants [26,41].…”
Section: Surface Tensionmentioning
confidence: 99%
“…Fourth, electrospinning enables the production of fibers with an infinite number of chemical compositions, and fifth, it also allows the production of different types of morphology by modifying the spinneret. With the combination of these properties, electrospun fibers can be utilized in biomedical applications [12,41,43,51,54,60,[77][78][79][80][81][82][83][84], filtration [39,[85][86][87][88], energy sectors [2,[89][90][91][92][93], sensors [5,26,[94][95][96][97], textiles, catalysis [26,98], and electrical applications [99,100]. Figure 7 shows the different types of nanofibers and their applications.…”
Section: Applications Of Electrospun Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a loss of the cones' characteristic shape due to intermixing of both internal and external fluids. To ensure the consistent and uniform encapsulation of the core within the shell, it is important to maintain a lower output rate for the core solution compared to that of the shell solution [34].…”
Section: Structure and Surface Morphologymentioning
confidence: 99%
“…Achieving sustained drug release using nanofibers composed of water-soluble polymer PVA is expected to be more challenging than that from nanofibers made from biodegradable hydrophobic polymers such as poly(lactic-co-glycolic acid) (PLGA) and poly(ε-caprolactone) (PCL). 8,9) Different grades of PVA having varying degrees of hydrolysis and polymerization could control the solubility of PVA nanofibers; however, there are few reports on this. By using the PVA grades, LZM release from various PVA nanofibers was evaluated in this study, as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%